Dietary tryptophan plays a role as an anti-inflammatory agent in european seabass (dicentrarchus labrax) juveniles during Chronic Inflammation - Azeredo, Rita (2024)
Where teleost fish are concerned, the effects of a dietary tryptophan surplus are mostly immunosuppressive, making it a potential dietary anti-inflammatory strategy. The goal of the present work was to evaluate the effects of tryptophan dietary supplementation on immune and neuroendocrine responses of the European seabass, Dicentrarchus labrax, undergoing chronic inflammation. Juvenile European seabass were intraperitoneally injected with an inflammatory agent (inflamed group) or a saline solution (control group). Within each group, fish were fed a control and a control-based diet supplemented with tryptophan for 4 weeks. Different tissues were sampled every week for the assessment of immune-related parameters. When tryptophan was provided to fish undergoing inflammation, the gene expression of a macrophage marker increased sooner and remained high until the end of the experiment. The same fish showed a concurrent increase in peripheral monocyte counts. After one week, molecular patterns of anti-inflammatory processes seemed to be favoured by tryptophan. Altogether, results show that a short administration period seems to be critical where tryptophan supplementation is concerned since at later inflammatory stages—and longer feeding periods—fish fed this diet displayed a molecular profile similar to that of fish fed a control diet.